Evaluation of treatments for Bartholin's cyst or abscess: a systematic review. (4th February 2020) - Illingworth, BJG; Stocking, K; Showell, M; Kirk, E; Duffy, JMN
Abstract : Background: No consensus on the management of symptomatic cysts or abscesses of the Bartholin's gland exists. Objectives: To assess the effectiveness and safety of surgical interventions for a symptomatic Bartholin's cyst or abscess. Search Strategy: We searched bibliographical databases from inception to April 2019. Selection Criteria: Randomised trials evaluating a surgical intervention for the treatment of a symptomatic Bartholin's cyst or abscess. Data Collection and Analysis: Eight trials, reporting data from 699 women, were included. Study characteristics and methodological quality were recorded for each trial. Summary estimates were calculated using random‐effects methods. Main Results: When considering the recurrence of a symptomatic Bartholin's cyst or abscess, the evidence was consistent with notable effects in either direction (risk ratio [RR] 0.76; 95% confidence interval [CI] 0.41–1.40) when comparing marsupialisation with incision, drainage and insertion of a Word catheter. Limited inference could be made when comparing marsupialisation with incision, drainage and silver nitrate insertion (RR 1.00; 95% CI 0.57–1.75), and incision, drainage and cavity closure (RR 0.25; 95% CI 0.01–4.89). There was limited reporting of secondary outcomes, including haematoma, infectious morbidity and persistent dyspareunia. Conclusions: Current randomised trial evidence does not support the use of any single surgical intervention for the treatment of a symptomatic cyst or abscess of the Bartholin's gland. Prospective Registration: PROSPERO: International Prospective Register of Systematic Reviews; CRD42018088553. Tweetable Abstract: Further research is needed to identify an effective treatment for #Bartholin's cyst or abscess. @jamesmnduffy Tweetable Abstract: Further research is needed to identify an effective treatment for #Bartholin's cyst or abscess. @jamesmnduffy. This article includes Author Insights, a video abstract available at https://vimeo.com/rcog/authorinsights16079